The Effect of Financial Management and Investment Decision on Firm Value with Profitability as a Mediating Variable - Henny A. Manafe; Tyahya Whisnu Hendratni; Subur Harahap; Ikramina Larasati Hazrati Havidz (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Firm value reflects market perceptions of a company’s performance and long-term sustainability. However, empirical evidence regarding the influence of financial management and investment decisions on firm value remains inconsistent, indicating that the underlying internal mechanisms are not fully understood. This study aims to examine the effects of financial management and investment decisions on firm value, incorporating profitability as a mediating variable for companies listed on the Indonesia Stock Exchange. A quantitative approach with a causal research design was employed, utilizing secondary data from annual financial statements covering the 2019–2023 period. Financial management and investment decisions were measured using financial structure and asset growth indicators, while profitability and firm value were assessed using profit performance ratios and market-based ratios. Data analysis was conducted through multiple linear regression, with mediation tested using the Sobel test. The results reveal that financial management and investment decisions do not consistently exert a direct effect on firm value but significantly influence it through enhanced profitability. These findings underscore the critical role of profitability as a mediating mechanism in value creation and provide practical implications for managers in formulating financial and investment policies that enhance profitability and long-term firm value.